Safety And Efficacy Of 4 Years Of Deferasirox Treatment For Sickle Cell Disease Patients. (February 2013) - Vlachaki, Efthymia; Mainou, Maria; Bekiari, Eleni; Vetsiou, Evaggelia; Tsapas, Apostolos
<x xml:space="preserve">Abstract</x> Deferasirox (DFRA) is a novel oral chelator agent for treatment of iron overload. Although well established in the treatment of β-thalassemia major (β-TM), it has not yet been fully investigated in patients with sickle cell disease. The aim of this report is to present the preliminary results of a pilot study assessing the effect of 4 years of DFRA treatment in six patients with sickle cell disease who are in need of recurrent transfusions. Our results show a significant reduction of ferritin levels and improvement of liver hemosiderosis, assessed by means of magnetic resonance imaging T2* (MRI T2*). None of the patients presented any serious adverse effects and the treatment was well tolerated. These results are in accordance with previous studies about the use of DFRA in sickle cell disease.